2023
DOI: 10.1108/ijhma-01-2023-0002
|View full text |Cite
|
Sign up to set email alerts
|

Young consumers' green marketing orientation: role of customer citizenship behaviour in determining real estate purchase intention in India

Abstract: Purpose The purpose of this paper is to assess green marketing as an influential factor in the purchase of real estate. In this study, the consumer citizenship behaviour of young individuals will be studied with an assessment of real estate purchase intention, strategic green marketing orientation (GMO) and tactical GMO. Design/methodology/approach The sample frame consists of young consumers from India’s metropolitan cities. The respondents were in the range of 18 to 35 years of age. These cities provide a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“…It is a rising idea in the construction industry that aims to promote environmental sustainability (Zahan et al, 2020). The concept of "green real estate" covers many activities that emphasize all eco-friendly relationships throughout the project cycle, such as project design, operation, manufacturing, maintenance, decoration and services (Jacob et al, 2023). They also found that in Indian residential real estate, companies focus on maintaining sustainable features, which include green building products, energy-efficient applications and solar panels, and encourage them with the help of green marketing campaigns.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is a rising idea in the construction industry that aims to promote environmental sustainability (Zahan et al, 2020). The concept of "green real estate" covers many activities that emphasize all eco-friendly relationships throughout the project cycle, such as project design, operation, manufacturing, maintenance, decoration and services (Jacob et al, 2023). They also found that in Indian residential real estate, companies focus on maintaining sustainable features, which include green building products, energy-efficient applications and solar panels, and encourage them with the help of green marketing campaigns.…”
Section: Introductionmentioning
confidence: 99%
“…Health Organization (WHO), over 80% of persons in urban regions still reside in air-polluted areas (Jacob et al, 2023). Therefore, the need for eco-friendly housing arises as it contributes to environmental preservation and offers health and community benefits to homeowners and society.…”
mentioning
confidence: 99%
See 3 more Smart Citations